Mindfulness-based supportive therapy on reducing suffering in patients with advanced cancer: randomised controlled trial - Tan, Seng Beng; Chee, Chung Huey; Ngai, Chin Fei; Hii, Siew Lin; Tan, Yi Wen; Ng, Chong Guan; David Paul, Capelle; Sheriza Izwa, Zainuddin; Loh, Ee Chin; Lam, Chee Loong; Chai, Chee Shee; Ng, Diana Leh-Ching (BMJ Publishing Group Ltd, 2022)
Objectives Suffering is common among patients with advanced cancer. The practice of mindfulness during patient care can potentially reduce suffering. We aimed to examine the efficacy of mindfulness-based supportive therapy (MBST) on reducing suffering in patients with advanced cancer. Methods We conducted a parallel-group, single-blinded, randomised controlled trial at the University of Malaya Medical Centre, Malaysia. Seventy-three patients with advanced cancer with an overall suffering score ≥4/10 based on the Suffering Pictogram were recruited and randomly assigned into either the MBST group (n=34) or the control group (n=39). Results There was a statistically significant reduction in the overall suffering score in the MBST group compared with the control group (U=432.5, median1 =−2.0, median2 =−1.0, z=−2.645, p=0.008). There was also significant improvement in the total Hospital Anxiety and Depression Scale score (U=483.5, median1 =−4.0, median2 =−3.0, z=−1.994, p=0.046), and the total Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being score (U=252.0, median1 =+14.5, median2 =+5.0, z=−4.549, p=0.000) in the MBST group compared with the control group. Conclusions The results provided evidence that the practice of MBST during patient care could promote positive psychosocial outcomes